Adherence to Recommended Breast Cancer Screening in Iranian Turkmen Women: The Role of Knowledge and Beliefs. (16th April 2013) - Charkazi, Abdurrahman; Samimi, Afieh; Razzaghi, Khadijeh; Kouchaki, Ghorban Mohammad; Moodi, Mitra; Meirkarimi, Kamal; Kouchaki, Ashoor Mohammad; Shahnazi, Hossein
Abstract : The aim of the current study was to investigate breast cancer screening performance among Iranian Turkmen women along with their knowledge and beliefs. A cross-sectional study was carried out in June to December 2011. Through clustered sampling method, 1080 Iranian Turkmen women completed the questionnaire including breast cancer screening adherence, knowledge, fatalism beliefs, and perceived threat using Champions Health Belief Model Scale (CHBMS).The mean age of the participants was 43.04 (SD = 11.80) years. Compliance rate in a regular basis based on national guidelines was 13.1%, 2.5%, and 0.9% for SBE, CBE, and mammography, respectively. A mere 4% have been provided adequately with information about breast cancer. Having knowledge was the best predictor of breast cancer screening adherence along with high educated husbands for SBE performing. Susceptibility and fatalism were low and were influenced by participants' educational level and age. In conclusion, Iranian Turkmen women had insufficient knowledge, low perceived susceptibility, high fatalistic belief, and very poor adherence to breast cancer screening. There is a need for providing breast cancer education programs among the Iranian Turkmen women to increase their adherence rate.